二氧化碳濃度偵測─手機結合QR Code與藍牙 - 陳榮靜; 林虹秀; 郭宏毅 (朝陽科技大學資訊學院, 2015)
近年來室內空氣健康危害的議題逐漸受重視，科技發達造成二氧化碳含量不斷增加，使氣候劇烈轉變，地球面臨種種危機。二氧化碳濃度含量過高影響環境以及人類，危害人體造成缺氧、手腳發麻、失去知覺甚至陷入昏迷導致窒息而亡。設計此系統主要是希望能夠隨時監控週遭環境的空氣品質，利用二氧化碳探測器結合現今日漸普及的智慧行動裝置及網路，使用者只要透過手機或電腦就可以清楚掌握數據，確認自己是否正處於安全舒適的空間環境，室內空間的二氧化碳濃度及溫度是否正常，並利用此系統有效的控管室內空氣品質及溫度。實驗證明我們所設計的系統，可有效達到二氧化碳濃度的監控，並能進一步結合室內空間設備或解決措施，達到室內空氣品質改善的功效。 During recent years, indoor air quality is being taken seriously, elevated levels of carbon dioxide after technology developed to make dramatic changes in climate and polar ice sheet disintegration. Global climate is suffering from environmental crises. High concentrations of carbon dioxide levels will have a bad effect on the environment and humans, may cause hypoxia, numb hands and feet, lose consciousness or even death. This system is mainly want to be able to monitor the ambient air quality at any place, and using carbon dioxide detectors combine the wisdom of mobile devices and networks, users can get information by using a mobile phone or computer, to confirm whether we are in safe and comfortable environment, also we can control the indoor air quality and temperature effectively by the system.